9 - 3 / ⅓ + 1 = ?

(( 9 * 3 ) - ( 3 * 3 ) / ( ⅓ * 3 ) + (1 * 3)) / 3 = 7

9 * 3 = 27

3 * 3 = 9

⅓ * 3 = 1

1 * 3 = 3

27 - 9 / 1 + 3 = 21

21 / 3 = 7

The answer I came up with is “7”

Would like to know if correct :3

9 - 3 / 1/3 + 1

9 - 9/3 / 1/3 + 1

9 - 9 * 3 / 3 * 1 + 1

9 - 27 / 3 + 1

9 - 9 + 1

= 1

Humm… I think I took a wrong turn somewhere… x.x

9 - 3 / ⅓ + 1 = ?

I was taught that when a multiplication or division shows up right after an addition or subtraction, you handle the former before addressing the latter. Thus, I figure I should first solve for 3 / ⅓. As for the steps…

## 3 / ⅓ =

##
3 / 1 → 3

/

1 / 3 → 1/3

When dividing two numbers, you’re basically asking “How many hops of the second number do I need to arrive at the first?” And thus I figured that 3 / ⅓ probably = 9, as 1/3 * 9 = 3.

And now the problem is:

9 - 9 + 1

Which would thus equal 1, as when you subtract a positive number by itself, you get 0.

So, there’s my thought process. Hope it’s not too silly lol

Oh, I like the hops approach. It looks much faster than making the whole number into a fraction. I’ll have to give that a try and see if my brain will cooperate ^^

Good luck! Now I just wish I knew what made the numbers so weirdly big in my post xD